Retention in HIV/AIDS Management Services: is it Really Poor? The Case of Yaounde Central Hospital in Cameroon - Charles Kouanfack, PhD; Fala Bede, MD; Claude Ngwayu Nkfusai, MSc; Emerson Wepngong, MD; Mbinkar Adeline Venyuy, MSc; Chombong Hubert, MSc; Denise Movuh Sam, MD; Samuel Nambile Cumber, PhD (Global Health and Education Projects, Inc., 2020)
Background: After consecutively defaulting on their appointments for three months, many HIV positive patients are often reported to have defaulted on their treatment, become lost to follow-up (LTFU), or no longer in care. We sought to determine if retention in HIV/AIDS care and treatment is really poor. Methods: Outcomes of patients with missed clinic appointments and reasons for missing appointments were studied. We sampled adult HIV positive patients on antiretroviral therapy (ART) who by clinic had missed their clinic appointments by more than four weeks between 1997 and 2019 at the HIV Care and Treatment Center (CTC) (Day Hospital) of the Yaoundé Central Hospital. We assumed that patients who missed their clinic appointment also missed some doses of their ART medications. Patients considered LTFU and those who had defaulted for two months were traced by telephone calls and home visits. Reasons for ART discontinuation were recorded for those who stopped or interrupted ART. Results: Of the 1139 patients who were either LTFU or who had defaulted for two months, 247/1139 (22 %) could not be traced. Out of the successfully traced patients, 50 (4%) had died and 798/1139 (70%) were alive and 310/1139 (27%) were on ART of which 35/1139 (3%) had developed informal ways of obtaining ART through clinic personnel. A good number were brought back to and reinitiated on ART after tracking (540/1139 or 47%). Of those known not to be on treatment(ART), 27/1139 (2%) had deliberately stopped ART and 63/1139 (6%) promised to return and took an appointment with CTC pyscho-social workers. Major reasons shared for missing clinic appointments were travel out of city (39%), distance from health facility, and financial cost for getting to health facility. Conclusion and Global Health Implications: Despite clinic data showing many patients had missed monthly appointments or were LTFU, we saw that a sizeable amount of such patients were actually in care and on ART. The above findings lead to the suggestion that clinic data used in program performance   Copyright © 2020 Kouanfack et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.